Linking a digital asset to an NFT. Technical and legal analysis (2024)
NFTs (non-fungible tokens) enable the commercialization of goods and services through blockchain technology, enhancing the security, transparency, and speed of transactions. The primary challenge NFTs face is their connection to the underlying asset, ensuring that transferring the token also means transferring the linked asset. This interdisciplinary article examines the technical and legal challenges of creating and linking a digital asset to an NFT. To explain the binding process, an NFT associated with a digital artwork was created, and relevant internal and uniform legal regulations were analyzed.